Product Preservation Design of Vegetable and Animal Food Processing - Menduza Burnd; Joffersen Yrick (Journal La Lifesci, 2021)
The aims of the research is determine the Product Preservation Design of Vegetable and Animal Food Processing. Packaging designed to preserve food components in the hands of customers while preventing contamination by bacteria and fungus is the goal. As long as food is stored properly, the quality of the food will deteriorate. Packaging is necessary in order to deliver the following information: Package must convey an accurate representation of its contents; it should neither be copied from other parties' packaging designs, nor should it be too complex, making it prohibitively costly to produce